Patient suitability for free water protocols in acute stroke and general medicine: a qualitative study of clinician perceptions. Issue 3 (23rd March 2022) - Murray, Joanne; Maloney, Shannon; Underdown, Kaitlyn; Doeltgen, Sebastian
Abstract: Background: The free water protocol (FWP) is an alternate management strategy for patients with dysphagia, who would otherwise be nil by mouth or prescribed thickened fluids, allowing them to drink and potentially aspirate water under strict guidelines to minimize the risk of adverse consequences. The FWP is not widely implemented in acute settings, and it is unclear whether this is due to the complexity of patient presentations, clinician decision‐making or barriers related to the setting. Aims: To explore the perceptions and decision‐making process of clinicians about using FWPs to manage dysphagia for patients admitted to acute stroke and general medicine. Methods & Procedures: A qualitative, critical realist approach was adopted to allow for in‐depth exploration of the perspectives of four dietitians, seven medical officers, eight registered nurses and 17 speech and language pathologists (SLPs) from three hospitals in a capital city of Australia. Data from semi‐structured interviews were analysed using the Situated Clinical Decision‐Making Framework (CDF). Outcomes & Results: Participants were cautious about FWP for patients with neurological conditions, head and neck cancer, dementia, poor immunity, chronic or recurrent respiratory illness, and certain types of stroke. Medical status and the implications for aspiration were paramount, particularly respiratory status, oxygen supplementation, cognitive status, fatigue and mobility. Participants considered patient quality of life, preferences and choices for care, but indicated that factors influencing safety often outweighed patient preference for water. Indirect factors affecting decision‐making included the roles of the multidisciplinary team, individual clinical experience and attitude to risk, and availability of supervision. Conclusions & Implications: Despite the benefits of FWPs in other settings, in acute stroke and general medicine, clinicians erred on the side of safety and, in most cases, would not implement an FWP. Future clinical research is needed to systematically design high‐quality and feasible clinical trials to determine the benefits and safety of FWPs for patients with dysphagia in these settings. This would lay the foundations for guidelines to support the complex clinical decision‐making regarding patient suitability for FWPs. WHAT THIS PAPER ADDS: What is already known on the subject: FWPs are an alternate management strategy for patients with dysphagia, with systematic reviews recommending their use for adults in inpatient rehabilitation with a low risk of pneumonia. However, evidence from the acute setting is sparse, leaving clinicians unsure about which patients might benefit and which may inadvertently be exposed to increased risk by an FWP. What this paper adds to existing knowledge: Participants from all interviewed disciplines agreed that SLPs lead the decision‐making process and as such act as 'gatekeepers' for access to an FWP. The decision‐making process is complex, and participants acknowledged that disease conditions and illnesses were often used as exclusionary criteria. Although participants reported favourably on the benefits of FWPs, their decision‐making privileged risk aversion over patient preference in most settings, except for palliative care. Lack of clinical guidelines and research evidence in acute care settings, as well as the focus on risk aversion, appear to perpetually reinforce the avoidance of FWP in these settings. Of note, more senior clinicians acknowledged being more deliberately guided by patient preference; hence, leadership by senior clinicians appears critical for change in practice in this space. What are the potential or actual clinical implications of this work?: If evidence about the safety of FWP in the acute settings is to be collected, a systematic approach to addressing the present barriers is warranted. This may allow rigorous clinical trials to proceed and potentially lead to best‐practice guidelines for dysphagia management options for wider populations of patients.